Multimethodology : an alternative management paradigm to process quality improvement. (2008)
This thesis is about the formulation of a structured sequence of events using a multimethodology approach to facilitate the intervention and subsequent management, of key factors contributing to the failure of management information system development projects undertaken in the financial services industry1. Furthermore, a clear distinction is made between information system development projects undertaken within the ambit of the broader development context of ‘information technology’, as opposed to information system development projects undertaken within the ambit of the financial services industry, the latter, the focus of this thesis. The formulation of the structured sequence of events serving as mitigating factors, was mooted specifically as a result of known failure factors of management information systems development projects undertaken in the financial services industry. In terms of this research, these factors fall into two mainstream categories2, namely: Ø The quality of business requirement functional specifications. Ø Change to business requirement functional specifications, while the latter is still in the process of being developed. From the field research undertaken for this thesis both locally and abroad, the analogy was drawn that the above two factors are normally juxtaposed, contributing to multi-faceted impacts to information system development project lifecycles. Key impacts point to not only the escalation of previously approved budgets, but also to extended timelines and already mapped processes. The research shows that these two entities would typically lead to an executive call for rework of not only the business case, but also of the processes supporting the whole development. This could invariable culminate in the termination of the project or culminate in extensive recoding and process changes, which in turn would lead to the requirement for extensive change management initiatives. Alternatively, the additional rework could result in benefits harvesting from the initiative to be delayed or severely impacted. This statement is made with the clear caveat, that should the rework result in end user effectiveness being significantly boosted as a result of the required rework, to the extent that the ratio of operating profit over the benefit life span of the system to total development cost be raised, it would undoubtedly quantify such rework. The structured sequence of events serving as mitigating factors to facilitate the intervention and subsequent management of key factors contributing to the failure of management information system development projects are formulated from selected key elements of the following system methodologies namely: Ø The ‘Capability Maturity Model’, which Herbsleb et al.5 defines as ‘a reference model for appraising software process maturity and a normative model for helping software organizations progress along an evolutionary path from ad hoc, chaotic processes to mature disciplined software’. Ø The ‘Balanced Scorecard’, which Kaplan & Norton6 defines as ‘a management system that can motivate breakthrough improvements in such critical areas as product, process, customer, and market development’. A multimethodology approach will be deployed in the formulation of the mitigating factors from the above listed systems methodologies, underpinned by the concept ‘system’. This then would be further enhanced by the author’s own contributions gleaned from experience spanning some 34 years in systems development for the financial services industry, both locally and abroad. These mitigating factors will come into play at two specific levels of a typical information technology project lifecycle namely: Ø At the formulation of business requirement functional specifications. Ø During the development and testing stages, which are typically associated with change in the systems development lifecycle. Using a multimethodology approach, the interrelationship of the various core entities, gleaned from the above listed system methodologies, ultimately supporting the structured sequence of events serving as mitigating factors are graphically depicted below. In addition, the mitigating factors are positioned to reflect their potential position in a typical systems development life cycle 7, commonly associated with information system development for the financial services industry. The purpose of this thesis is then to determine if a set of mitigating factors can be developed from a structured sequence of events using a multimethodology approach to facilitate the intervention and subsequent management of key factors contributing to the failure of management information systems development undertaken in the financial services industry. Furthermore, the thesis proposes that the structured set of mitigating factors be incorporated as an alternative methodology within the ambit of the greater information technology project management life cycle for all project initiatives in the financial services industry. === Prof. N. Lessing